2018
DOI: 10.1152/jn.00351.2017
|View full text |Cite
|
Sign up to set email alerts
|

Calcium dynamics control K-ATP channel-mediated bursting in substantia nigra dopamine neurons: a combined experimental and modeling study

Abstract: Burst firing in medial substantia nigra (mSN) dopamine (DA) neurons has been selectively linked to novelty-induced exploration behavior in mice. Burst firing in mSN DA neurons, in contrast to lateral SN DA neurons, requires functional ATP-sensitive potassium (K-ATP) channels both in vitro and in vivo. However, the precise role of K-ATP channels in promoting burst firing is unknown. We show experimentally that L-type calcium channel activity in mSN DA neurons enhances open probability of K-ATP channels. We then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 66 publications
1
34
0
Order By: Relevance
“…The KATP channel is highly expressed in dopaminergic neurons in the midbrain and regulates dopamine release. These neurons project to the frontal cortex and hippocampus [45][46][47][48][49][50] . Recently we confirmed that dopamine regulates NEP…”
Section: Discussionmentioning
confidence: 99%
“…The KATP channel is highly expressed in dopaminergic neurons in the midbrain and regulates dopamine release. These neurons project to the frontal cortex and hippocampus [45][46][47][48][49][50] . Recently we confirmed that dopamine regulates NEP…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that our patch pipette solution sufficiently approximated an unperturbed intracellular in vivo milieu of individual midbrain dopamine neurons regarding buffering (e.g. calcium) as well as energy and redox metabolism, which are tightly coupled to excitability (Knowlton et al, 2018;Schiemann et al, 2012;Subramaniam et al, 2014). In addition, once the standard whole-cell configuration was established, electrical discharge properties remained stable for at least a few minutes ( Fig.…”
Section: Resultsmentioning
confidence: 65%
“…The selective vulnerability of DA neurons of the substantia nigra pars compacta (SNpc; Box 1) has been the focus of research (Burbulla et al, 2017; Guzman et al, 2010; Liss et al, 2005) leading to the concept that autonomous pacemaking (Box 1) in these neurons leads to sustained calcium influx through L-type calcium channels (Surmeier et al, 2011). Cytosolic calcium overload causes mitochondrial oxidative stress (Dryanovski et al, 2013) and subsequent redox modification of ATP-sensitive potassium channels (K-ATP) (Knowlton et al, 2018) that control the spontaneous tonic pacemaker activity (Liss et al, 2001, 2005; Schiemann et al, 2012), which may lead into a vicious cycle. Although nociceptive neurons are not spontaneously active, L-, N- and T-type voltage-gated calcium channels and K-ATP essentially contribute to the enhancement (calcium channels) (Alles et al, 2018; Candelas et al, 2019; Choi et al, 2016; Neugebauer et al, 1996) or lowering (K-ATP) of nociceptive neuron excitability (Kawano et al, 2009; Rodrigues and Duarte, 2000).…”
Section: Nociceptive Neurons In Pdmentioning
confidence: 99%